Le « retour à la terre » : entre utopie et nostalgie - Madeleine Sallustio (Conserveries Mémorielles)
Often criticized because of its conservative overtones, nostalgia emerges from time to time in social discourses, especially in times of social, economical, political or ecological crisis. Yet, nostalgia also brings with it a wish for utopian projects and a significant critical potential.Among the common discourses about the lost past, the traditional rural world is one of the most frequently invoked topic. The small-scale farmer is presented as an emblem of stability and harmony. Indeed, France has been the scene of various “back-to-Nature” movements and of connected activities (organic agriculture, goat farming, handicraft, …) that are still undertaken by libertarian anarchists; heirs of Mai, 1968; or people in search of ecological coherence and independence.This study is about the articulation of the rural nostalgia and the utopian aspirations of the contemporaneous “back-to-Nature” project. Utopian and nostalgic imaginations feed each other and allude to an unloved present while, at the same time, proposing the creation of a radical alternative that involves the entire existence. Therefore, the temporality in which the actors are living seems to oscillate between past, present and future.